The The Effect of Islamic Financial Inclusion and Literacy on the Productivity of MSMEs: Case Study in Probolinggo - Muhammad Alfan Rumasukun; Alivia Maharani (University of Darussalam Gontor, 2024)
Looking at the large contribution of MSMEs to GDP growth, namely 0.2%, it can be seen that the market in this sector is supported by a fairly large portion of the workforce, reaching 96.92%. However, the low productivity of MSMEs is a concern because the input produced is not commensurate with the output produced. This research aims to investigate and understand the productivity problems faced by MSMEs (Micro, Small and Medium Enterprises) in Probolinggo, especially in Mayangan sub-district. This research covers aspects such as financial inclusion and financial literacy, with a focus on sharia approaches. This was done to understand the impact of sharia financial inclusion and sharia financial literacy on the productivity of MSMEs in the region. The study employs quantitative research methods and utilizes primary data obtained from respondent-filled questionnaires. The population consists of MSMEs in the Mayangan District, with 30 respondents selected through Probability Sampling. Then the data is processed using multiple linear regression analysis techniques using the SPSS (Statistical Package for Social Sciences) program. The results of this study indicate that Islamic financial inclusion and Islamic financial literacy have a significant effect on the productivity of MSMEs. This is evidenced by the result of the coefficient of determination analysis where the variables of Islamic financial inclusion and Islamic financial literacy affect MSMEs productivity by 84,3% and the remaining 15,7% is explained by other variables not included in this study.